BAKTERI PENGGUNA METIL MERKURI PADA SEDIMEN DAN AIR SUNGAI TERCEMAR TAILING HASIL PENAMBANGAN EMAS DI SELODONG LOMBOK BARAT - , Evredy Wondiwoi, S. Pd, Prof. Dra. Endang Sutariningsih Soetarto, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Tailing derived from gold mining have potential as hazardous pollutants to the environment and human health, because it contains of various metal especially mercury. The pollutants accumulated in the river bottom mixed with the river sediment. The sediment is object of this research because it contains the tailings used as the kemolitrotrof habitat especially bacteria resistant to mercury, particularly methylmercury. It is highly toxic to all organisms, including microbes, only a few types of bacteria able to survive and transforming the metals into the less toxic forms. This research aims to obtain indigenus bacteria resistant to methylmercury, and examine the capability of these bacteria grow in several concentrations of methylmercury. The research started with taking sediment samples containing gold mining tailings as the bacterial source of methylmercury user. The methylmercury utilizing bacteria were isolated through enrichment culture technique, using column reactor filled with liquid medium of Nutrient Broth (NB), supplemented with 0,1 mg/L CH3HgCl. After several sub-cultures, the bacteria were isolated through dilution series and plated on Agar Nutrient (NA) containing 0.1g/L CH3HgCl using pour plate techniques. The colonies growth separately was taken and transferred on to agar slant as single culture. The isolate selection was carried out based on their grow ability on various concentrations of CH3HgCl. At time intervals, the bacterial growth was monitored spectrophotometrically (Î»600nm) and the total concentrations of mercury in the bacterial culture were measured using an Atomic absorption spectrometer (AAS). Isolates having a short of generation time (g) and the high growth rate (Î¼) were selected and identified using standard Bergeyâs Manual of Systematic Bacteriology. The research results obtained thirteen isolates suspected as the methylmercury user. Only three isolates (BPM-001, BPM-008 and BPM-008- 013) were able to grow relatively rapid as with by maximum specifik growth rate (Î¼max) about 0,752/hour,thereby can be presumed the methilmercury has inhibitor of the growth. The three isolates had been identified similar to Seratia marcescen, (BPM-001), Psudomonas aeruginosa, (BPM-008) and Enterobacter cloaceae, (BPM-013). These isolates were able to grow on methylmercury concentration up to 4 mg/L.